O10 REINFORCED TENSION LINE SUTURE RESULTS IN LOW INCISIONAL HERNIA RATE AFTER CRS/HIPEC OPERATIONS. (25th November 2021) - Wenzelberg, Charlotta; Petersson, Ulf; Syk, Ingvar; Rogmark, Peder
Abstract: Aim: Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal carcinomatosis entails several risk factors for incisional hernia (IH). At our institution fascia closure has been performed in a 4:1 manner with a 2-0 polydiaxanone suture (the PDS-group) or a 2-0 polypropylene preceded by a reinforced tension line (RTL) suture (the RTL-group). Our hypothesis was that reinforcing the suture line results in fewer IH at one year. Material and Methods: Single-center retrospective study on primary CRS/HIPEC 2004-2019. CT-diagnosed IH one year ±3 months postoperative. Additional data retrieved from clinical records and a prospective CRS/HIPEC database. Results: Of 193 patients, 63 were not evaluable for IH of which two, both in the PDS-group, were reoperated for fascial dehiscence (FD). 130 patients; 83 (45 women) in the PDS- and 47 (23 women) in the RTL-group, mean age 57 years (19-77) remained. RTL-patients were five years younger (54 vs 59), had a higher Karnofsky index and less bleeding (807 vs 1409 mL). No differences regarding sex, BMI, recent midline incisions, excision of midline scars, peritoneal cancer index score, complications (Clavien-Dindo 3b or higher), neo-adjuvant or adjuvant chemotherapy were found. Twelve IH (9%) were found, 11 (13%) in the PDS- and 1 (2%) in the RTL-group (p = 0.055). Conclusions: Despite many potential IH risk factors, the overall IH-incidences do not seem higher than after laparotomies in general. The RTL-group showed 2% IH compared to 13% in the PDS-group. The PDS-group were further burdened by two FD. The results are clinically relevant, suggesting an advantage with RTL-closure for these patients.